2022
DOI: 10.35848/1347-4065/aca3e5
|View full text |Cite
|
Sign up to set email alerts
|

Thermal neutron scintillation improvement in Ce:Li6Y(BO3)3 single crystals by thermal treatment

Abstract: Efficient, low-cost, and stable solid-state materials for portable thermal neutron detection are highly expected in order to substitute the currently used 3He and BF3 tank detectors. Li-glasses and halide compounds have emerged as candidates, however, they present critical drawbacks for practical implementations. Ce:Li6Y(BO3)3 is a promising oxide candidate that however has been disregarded due to its negligibly low light yield, caused by a poor crystalline and optical quality. In this study, we demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In a precedent publication, it was shown that the scintillation properties of LYBO can be drastically improved after air annealing close to the T m of LYBO. 11) Though this treatment causes a remarkable reduction in the concentration of scattering centers in LYBO, the latter do not represent the main source of non-radiative recombination, as will be seen later in the case of scattering-free crystals. In order to visualize the remaining scattering after annealing, a He-Ne laser with a five times higher power than a laser pointer was used.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…In a precedent publication, it was shown that the scintillation properties of LYBO can be drastically improved after air annealing close to the T m of LYBO. 11) Though this treatment causes a remarkable reduction in the concentration of scattering centers in LYBO, the latter do not represent the main source of non-radiative recombination, as will be seen later in the case of scattering-free crystals. In order to visualize the remaining scattering after annealing, a He-Ne laser with a five times higher power than a laser pointer was used.…”
mentioning
confidence: 94%
“…Ce-doped Li 6 Y(BO 3 ) 3 (LYBO) stands out as a promising alternative. 10,11) Compared with other candidates, it compromises a priori of all required basic material properties: a high Li content (3.06 × 10 22 cm -3 ), good chemical stability, a trivalent site (Y 3+ ) for efficient Ce 3+ doping, cheap and abundant constituents, and the possibility to grow large single crystals for low-cost mass production. Despite these promising characteristics, the poor crystalline and optical quality of Ce:LYBO crystals has largely discouraged its development for scintillation applications so far.…”
mentioning
confidence: 99%
See 3 more Smart Citations